2013
DOI: 10.1112/blms/bdt045
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Haagerup property by fibred coarse embedding into Hilbert space

Abstract: We show that a finitely generated, residually finite group has the Haagerup property (Gromov's a‐T‐menability) if and only if one (or equivalently, all) of its box spaces admits a fibred coarse embedding into Hilbert space. In contrast, the box spaces of a finitely generated, residually finite hyperbolic group with property (T) do not admit a fibred coarse embedding into Hilbert space, but do admit a fibred coarse embedding into an ℓp‐space for some p>2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
55
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 36 publications
(57 citation statements)
references
References 14 publications
2
55
0
Order By: Relevance
“…where m denotes a coarse disjoint union (see [MS13,Definition 2.17.(2)] and Subsection 3.2). Chen-Wang-Wang [CWW13] showed that G admits a fibred coarse embedding into a Hilbert space if and only if G is a-T-menable. They also showed that for a metric space M , if G is a-M -menable, then G admits a fibred coarse embedding into M .…”
Section: Introductionmentioning
confidence: 99%
“…where m denotes a coarse disjoint union (see [MS13,Definition 2.17.(2)] and Subsection 3.2). Chen-Wang-Wang [CWW13] showed that G admits a fibred coarse embedding into a Hilbert space if and only if G is a-T-menable. They also showed that for a metric space M , if G is a-M -menable, then G admits a fibred coarse embedding into M .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in [12] G. Kasparov and G. Yu showed that groups admitting coarse embeddings into uniformly convex Banach spaces satisfy the Novikov conjecture. Inspired by the above works, we extend further the result in [6]: for a residually amenable group G, we give a sufficient condition of the proper isometric affine action of G on some uniformly convex Banach space by fibred cofinitelycoarse embeddability of its box families. Theorem 1.1.…”
Section: Introductionmentioning
confidence: 84%
“…While it is theoretically appealing that we can, in particular, characterise many geometric properties of groups by geometric properties of their box spaces (so far, one could do that for ‘group‐theoretic’ or ‘equivariant’ properties like amenability or the Haagerup property and, more generally, property PB ), we are mostly interested in applications of this new notion. These are provided, in the case of asymptotic dimension, by a recent result of Yamauchi , which we formulate at the end of this section using the general language developed here.…”
Section: Asymptotically Faithful Coverings and Piecewise Propertiesmentioning
confidence: 99%
“…but as there is no dependence on y, it simply means that δ(γ) := δ(γ, y) is a homomorphism. In particular, inequality (8) means that the kernel F of δ is finite, as contained in the ball B(e, CA). Similarly, the existence of elements δ 0 ∈ Δ satisfying formula (7) and with uniformly bounded length (for example, |δ 0 | A as above) is equivalent to saying that the subgroup δ(Γ) is of finite index in Δ.…”
Section: Quasi-isometry Induced By One Mapmentioning
confidence: 99%
See 1 more Smart Citation